Selective patient experience with the Blom‐Singer Dual Valve voice prosthesis. (7th August 2017) - Brownlee, Ben; Ahmad, Saniya; Grammer, Tracy; Krempl, Greg
Abstract : Objectives/Hypothesis: This study compares the overall durability, phonation effort, and speech quality achieved by the Blom‐Singer Dual Valve prosthesis to the same characteristics achieved by the single‐valve prosthesis used in a select population of total laryngectomy patients who have demonstrated single‐valve prosthesis failure within 3 months of placement. Study Design: Prospective phase IV study. Methods: Fourteen patients who had previously experienced early valve failure using a single‐valve prosthesis had a Dual Valve placed by a speech language pathologist. A total of seventeen Dual Valves were inserted during routine clinical visits for valve replacement. Time intervals from insertion to replacement of the Dual Valve, as well as the average lifespan of patients' three previous single valves were collected. Subjective, categorical responses to speech quality and phonation effort for the Dual Valve compared to the single valve were collected on a questionnaire upon failure of the device. Results: The mean duration of the single valve was 60 days, with a median of 51 days, whereas the mean duration of the Dual Valve was 164 days, with a median duration of 84 days. Both sets of data were statistically significant, with a P value of .0131. Valve life was increased in 86% of patients, with 43% experiencing greater than 150 days improvement in valve duration when using the Dual Valve. Phonation effort was increased in 14% of patients, and speech quality was not significantly affected in any patients. Conclusions: In this select population, the Dual Valve offers improved durability over the single valve without sacrificing speech quality, making it a preferred prosthesis option for patients experiencing single‐valve failure in less than 3 months. Level of Evidence: 4. Laryngoscope, 128:422–426, 2018